Analysis of Brownfield Sites in the Villages and Towns in the Czech Republic - Jaroslav Škrabal; Kamila Turečková; Jan Nevima (Transylvanian Review of Administrative Sciences, 2021)
The issue associated with the situation of brownfields around the world is a very current topic today. This article focuses on the situation of the existence of brownfields in the Czech Republic. The aim of this article is to assess the current situation of brownfields from the perspective of municipalities and cities in the Czech Republic. The data in the paper were collected by means of a questionnaire applied to towns and villages in the Czech Republic. The existence of brownfields in regions can have a negative impact on the development of the relevant areas, such as villages, towns or higher-level administrative units. The research took place from 9 July 2018 to 31 January 2019. The rate of return on the primary research was 43.2% of the respondents. The results showed that brownfields mainly occur in former industrial regions. The predominant form of ownership of abandoned buildings and grounds was private ownership. It can be stated that agricultural, industrial activity and former civic amenities dominated in the previous use. Last but not least, the study points to regional differences that are noticeable between municipalities and cities in individual NUTS 3 regions in connection to the issue of brownfields.